The suitability of gold as a high quality liquid asset - Bayram, Kamola; Abdullah, Adam (GBSE, 2015)
The 2008-2009 global financial crisis affirmed that most of the commercial banks do not have enough liquid assets to withstand liquidity risk associated with financial stress. Therefore, in December 2010 the Basel Committee of Banking Supervision (BCBS) introduced two new ratios, the Liquidity Coverage Ratio (LCR) and the Net Stable Funding Ratio (NSFR) to ensure that banks have an adequate amount of High Quality Liquid Assets (HQLA) during times of financial turmoil. Gold, however, has so far not been included in the HQLA stock. This study examines each of the characteristics of HQLA and analyses how gold cope with them. Our results suggest that except of the one factor, which is low volatility, gold has no restrictions to be accepted as HQLA. Furthermore, the volatility of gold is an inverted asymmetric volatility to positive and negative shocks, such as positive shocks increase the volatility by more than negative shocks. Which means that the price of gold tends to rise during the times of financial distress thus making it an ideal hedge and safe haven asset which should be included in HQLA stock.